On language representation of spacial concepts - I N Ivashkevich (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2010)
The paper is dedicated to language representation of spatial concepts nominating specific areas of land (the names of bogs) in modern English. The author pays special attention to the role of perceptual features within the semantic structure of these concepts which constitute such basic ontological category as space.